Research into the process of loading the surface of a vibrosieve when a loose mixture is fed unevenly - Piven, Mykhailo; Volokh, Vadim; Piven, Alyona; Kharchenko, Sergei (Eastern-European Journal of Enterprise Technologies, 2018)
The work examines the influence of uneven feeding of a loose mixture on the process of loading a vibrating sieve. In this work, we established regularities of layer thickness, longitudinal and transverse components of velocity, density of loose mixture and specific load on the entire area of a vibrating sieve at uneven feeding at the inlet. The uneven feed was assigned by using a convex profile, a concave profile, and a triangular profile of the initial velocity for width at the inlet of a sieve. Flow characteristics change equally along the length of a sieve for the profiles considered. Flow characteristics change according to the initial velocity profile for width of the sieve. For a convex profile, the thickness is constant, the surface density and the longitudinal component of the velocity are the greatest along the longitudinal axis of the sieve, and they are the smallest near the side walls, the direction of the transverse component of the velocity is from the longitudinal axis to the side walls. For a concave profile, the thickness is constant, the surface density and the longitudinal component of the velocity are the greatest along the side walls, and they are the smallest along the longitudinal axis, the direction of the transverse component of the velocity is from the side walls to the axis. For a triangular profile, the thickness is constant, the surface density and the longitudinal component of the velocity are the greatest along one side wall, and they are the smallest along the opposite wall, the direction of the transverse component of the velocity is toward the first mentioned side wall. For a convex profile of the initial velocity, the surface is overloaded along the longitudinal axis of the sieve and it is underloaded along the side walls. For a concave profile, the surface is overloaded near the side walls, and it is underloaded along the longitudinal axis of the sieve. For a triangular profile - the surface is overloaded along one side wall and it is underloaded along the opposite one. The largest deviations of the specific load occur near the inlet section of the flow, the smallest ones - near the outlet section. The regularities of distribution of the specific load of the sieve are decisive in the design of feeders and distributors of loose mixtures, as well as in calculation of separation modes